Colocalization of vitiligo and alopecia areata presenting as poliosis. (23rd December 2014) - Walker, Addie; Mesinkovska, Natasha Atanaskova; Boncher, Julia; Tamburro, Joan; Bergfeld, Wilma F.
<x xml:space="preserve">Abstract</x> Vitiligo and alopecia areata are two cutaneous diseases believed to be primarily autoimmune in pathogenesis. While the coexistence of the two conditions in the same patient has been well‐described, reports of the two disease processes occurring in the same location are rare. We report the case of a 10‐year‐old male with an unremarkable past medical history who presented with a single localized area of poliosis with depigmented underlying skin on the frontal scalp. The hair in the affected area was relatively decreased in density. A punch biopsy of the depigmented patch demonstrated features consistent with both vitiligo and alopecia areata. The decreased number of large hair follicles and a focal peribulbar lymphocytic infiltrate around an anagen follicle were suggestive of alopecia areata. A panel of melanocyte‐specific stains revealed absent melanocytes in the epidermis, consistent with vitiligo. Loss of microphthalmia‐associated transcription factor‐positive root sheath cells was seen, suggestive of loss of melanocyte stem cells. The combination of clinical and histopathologic findings supports the theory of a common pathogenesis of alopecia areata and vitiligo.